Effect of biotin on growth performance, serum biochemical profiles, and histomorphological changes in acetate gossypol-treated mice - Luo, Qiyu; Xu, Tongxiang; Ainiwaer, Zulibina; Fan, Wenpeng; Wang, Caidie (Frontiers in Veterinary Science, 2025)
The objective of this study was to determine the effects of biotin on growth performance, serum biochemical profiles, and morphology of acetate gossypol-treated mice. Seventy-five healthy male Kunming mice were randomly assigned to five treatment groups: the control group (C), the biotin control group (BC), the acetate gossypol control group (AGC), the biotin prevention group (BP) and the biotin treatment group (BT). The study examined the growth performance, visceral index, serum biochemical profiles and histomorphological changes of mice. The results showed that compared with AGC group mice, the average daily feed intake of BP group and BT group increased by 40.47 and 45.69% (p < 0.05). Biotin prevention reduced the elevated blood urea nitrogen (BUN) levels in acetate gossypol-treated mice, biotin treatment reduced the elevated serum aspartate aminotransferase (AST), total protein (TP) and BUN levels in acetate gossypol-treated mice (p < 0.05). Biotin increase the values of villus height/crypt depth in duodenum and jejunum (p < 0.05). In conclusion, biotin potentially increase the growth performance of acetate gossypol-treated mice, it also has a positive effect on serum biochemical profiles, and histomorphological of acetate gossypol-treated mice.